PENDAMPINGAN UNTUK MENGEMBANGKAN DESA WISATA BERKUALITAS DI DESA KOTO RUANG, KECAMATAN IV KOTO, KABUPATEN ROKAN HULU - Raksapati, Abadi; Rugarmika, Rikeu (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2026)
Koto Ruang Tourism Village is a pioneer tourism village that is currently improving its institutional capacity and the quality of its tourism products to become a high-quality tourism village in terms of institutions, environmental management, and cultural management. This village has tourism resources in the form of natural landscapes, including rice fields and plantations, the Rokan River, and Tabur Hill, which are already well known as adventure tourism attractions. However, the village's main advantage is the presence of Rokan Palace, which has great potential to be developed as a high-value cultural tourism attraction due to its significant historical value as one of the remaining palaces in Riau Province. The community service carried out in Koto Ruang Tourism Village uses a participatory approach that involves all stakeholders being actively engaged in the process. This community service has succeeded in encouraging the merger of three previously existing Pokdarwis into one, namely Pokdarwis Sawah Koto, which represents Koto Ruang Tourism Village. Furthermore, the capacity of managers and institutions has been enhanced through a series of successful training sessions. Meanwhile, to improve the quality of tourism products, interpretation training, the development of tour packages, and tour package trials have been successfully conducted to determine the extent to which the managers of Koto Ruang Tourism Village are ready and capable of managing tour packages to be offered to tourists. In the future, further assistance and support from various parties will be needed to ensure the sustainability of Koto Ruang Tourism Village as a high-quality tourism village.Desa Wisata Koto Ruang merupakan desa wisata rintisan yang tengah meningkatkan kapasitas kelembagaan serta meningkatkan kualitas produk pariwisata yang dimiliki agar menjadi desa wisata berkualitas dari sisi kelembagaan maupun pengelolaan lingkungan dan budaya. Desa ini memiliki sumber daya wisata berupa bentang alam persawahan dan perkebunan, Sungai Rokan, hingga Bukit Tabur yang sudah cukup dikenal sebagai daya tarik wisata petualangan. Namun keunggulan utama desa ini adalah keberadaan Istana Rokan yang sangat potensial dikembangkan sebagai daya tarik wisata budaya bernilai tinggi karena memiliki nilai sejarah tinggi serta salah satu istana yang masih tersisa di Provinsi Riau. Pengabdian yang dilakukan di Desa Wisata Koto Ruang menggunakan pendekatan partisipatif yang melibatkan seluruh pemangku kepentingan untuk terlibat aktif dalam prosesnya. Pengabdian ini berhasil mendorong peleburan tiga Pokdarwis yang sebelumnya ada menjadi satu Pokdarwis Sawah Koto yang akan menjadi representasi Desa Wisata Koto Ruang. Selain itu peningkatan kapasitas pengelola dan juga kelembagaan melalui serangkaian pelatihan berhasil dilakukan. Sementara itu untuk meningkatkan kualitas produk pariwisata, pelatihan interpretasi, penyusunan paket wisata hingga uji coba paket wisata telah berhasil dilakukan untuk melihat sejauh mana pengelola Desa Wisata Koto Ruang siap dan mampu mengelola paket wisata yang akan dijual kepada wisatawan. Kedepan pendampingan lanjutan dan juga dukungan dari berbagai pihak terkait untuk memastikan keberlanjutan Desa Wisata Koto Ruang sebagai desa wisata yang berkualitas sangat diperlukan.